Atividade antioxidante de fucanas e galactanas extraídas de algas marinhas - Souza, Micheline Cristiane Rocha de (2008)
Studies made with polysaccharides of seaweed have demonstrated that these present important biological and pharmacological activities. These composites had presented "scavenging" activity of free radicals, which is important in the mediation of the inflammatory process and in the pathology of diverse disease. Recently, this "scavenging" property has taken some researches to evaluate the antioxidant capacity from various polysaccharides. Considering the limited research with polysaccharides and knowing its largely employed by the pharmaceutical and foodstuffs industries, we have objective to verify the actions from fucans and galactans as antioxidants. The fucans are found in brown seaweed and the galactans (carrageenans) in red seaweed. The fucans were obtained from seaweed Padina gymnospora (F0.5 e F1.1 fractions), common to our coastline and one another fucan, fucoidan, was of origin commercial and extracted from seaweed Fucus vesiculosus. The λ, κ e ι carrageenans were also of origin commercial. The antioxidant activities were tested in superoxide and hydroxyl systems to generated free radicals and for the inhibition of the lipid peroxidation. The results obtained to inhibition of formation the superoxide radicals demonstrated that all polysaccharides presented scavenging activity of superoxide radicals. The fucoidan, F0.5 and F1.1 fractions presented IC50 of 0.058; 0.243 and 0.243 mg/mL, respectively, while IC50 of the λ, κ and ι carrageenans were 0.046; 0.112 and 0.332 mg/mL, respectively. The results to inhibition of formation the hydroxyl radicals demonstrated that all sample had low effect in the inhibition of the formation of these radicals, except the F0.5. For these radicals the IC50 were 0.157 and 0.353 mg/mL to the fucoidan and F1.1, respectively and 0.357; 0.335 and 0.281 mg/mL to λ, κ and ι carrageenans, respectively. All the samples were capacity to inhibition the peroxidation, it present the IC50 of 1.250; 2.753 and 2.341 mg/mL to fucoidan, F0.5 and F1.1, respectively. Already the λ, κ and ι carrageenans presented the IC50 of 2.697; 0.323 and 0.830 mg/mL, respectively. With these findings, we conclude that polysaccharides used in this study presented activity antioxidant, and that fucoidan and the λ carrageenan show a significant "scavenging" activity for the radicals superoxide and the κ carrageenan a significant inhibitory activity for the lipid peroxidation